Staging Therapeutic Enactment with Veterans in Contact!Unload. Issue 4 (1st October 2020) - Lea, Graham W.; Belliveau, George; Westwood, Marv
ABSTRACT: This article shares an excerpt from the research-based theatre production Contact!Unload . The play, developed with military veterans using community theatre approaches, explores experiences of veterans transitioning from active service and living with trauma-related stress injuries. The excerpt included in this article provides a theatricalized example of therapeutic enactment (TE), a central intervention of the Veterans' Transition Project (VTP). After contextualizing both TE and VTP, the script provides a visceral example of one veteran's experiences both in service and in a TE. This article provides an example of using TE with veterans living with traumatic stress injuries and, in doing so, demonstrates the potential of research-based theatre as a methodology for engaging in and sharing psychological research.